2018
DOI: 10.1016/j.yexcr.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-derived neurons profiling reveals GABAergic circuit disruption and acetylated α-tubulin defect which improves after iHDAC6 treatment in Rett syndrome

Abstract: Mutations in MECP2 gene have been identified in more than 95% of patients with classic Rett syndrome, one of the most common neurodevelopmental disorders in females. Taking advantage of the breakthrough technology of genetic reprogramming, we investigated transcriptome changes in neurons differentiated from induced Pluripotent Stem Cells (iPSCs) derived from patients with different mutations. Profiling by RNA-seq in terminally differentiated neurons revealed a prominent GABAergic circuit disruption along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 64 publications
2
46
0
2
Order By: Relevance
“…Indeed, we have recently shown that in the absence of MeCP2, microtubule polymerization from centrosomes is impaired (Bergo et al , ). In good accordance, a reduction in microtubule stability associated with decreased α‐tubulin acetylation, caused by increased levels of HDAC6, was reported (Xu et al , ; Gold et al , ; Delépine et al , ; Landucci et al , ). Real‐time RT–PCR suggested that a post‐transcriptional mechanism is involved in the observed HDAC6 upregulation (Delépine et al , ) and our unpublished data confirm that Hdac6 mRNA levels are not perturbed in the Mecp2 null brain.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, we have recently shown that in the absence of MeCP2, microtubule polymerization from centrosomes is impaired (Bergo et al , ). In good accordance, a reduction in microtubule stability associated with decreased α‐tubulin acetylation, caused by increased levels of HDAC6, was reported (Xu et al , ; Gold et al , ; Delépine et al , ; Landucci et al , ). Real‐time RT–PCR suggested that a post‐transcriptional mechanism is involved in the observed HDAC6 upregulation (Delépine et al , ) and our unpublished data confirm that Hdac6 mRNA levels are not perturbed in the Mecp2 null brain.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, we suspect that HDAC6 inhibition under conditions lacking robust tau pathology might alter the acetylation status of non-tau HDAC6-dependent substrates (e.g., tubulin, cortactin, Hsp90) and thus restore axonal transport and MT-dependent trafficking, for example in the presence of Aβ (as we observed in the 5xFAD model) 50 . Indeed, loss or inhibition of HDAC6 was reported to stabilize MTs and improve axonal transport in nontauopathy syndromes including Charcot Marie Tooth (CMT) neuropathy 51,52 , amyotrophic lateral sclerosis (ALS) 53 , Rett syndrome 54 , and Aβ plaque deposition 19 .…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the biological mechanisms implicated in disease pathogenesis, we established and characterized a human neuronal model based on genetic reprogramming of patient fibroblasts into induced Pluripotent Stem Cells (iPSCs) [ 14 16 ]. iPSCs are a valuable source of patient-derived cells like neurons, which represent the most relevant cell type for studying disease mechanisms as well as for testing innovative therapeutic approaches, such as gene editing.…”
Section: Introductionmentioning
confidence: 99%